TO STUDY AND MITIGATE DELAYS IN MEGA CONSTRUCTION PROJECTS IN KHYBER PAKHTUNKHWA (KPK) THROUGH FAST TRACKING TECHNIQUE: A CASE STUDY OF BUS RAPID TRANSIT (BRT) PESHAWAR - Abdullah; Inamullah Khan; Muddasir Abbas; Prof. Dr. Syed Muhammad Ali; Prof.Dr. Khan Shahzada; Dr. Fawad Ahmad (Spectrum of Engineering Sciences, 2025)
The issue of delays in mega constructions has been an unending challenge, especially in developing countries such as Pakistan, which leads to time overruns, cost escalation, and compromised quality. This study examines the key causes of delays through a detailed case study of the Bus Rapid Transit (BRT) Peshawar project, aiming to examine, analyze, and propose practical solutions for delay mitigation in mega construction projects. Data was collected through an organized questionnaire and interviews with key stakeholders involved in the project. The qualitative and quantitative mixed approach in addition to Relative Importance Index (RII) approach was applied. This study reveals that the most remarkable causes of delay are scope changes with a Relative Importance Index (RII) value of 0.767, design-related issues with an RII of 0.733, and limited availability of resources with an RII of 0.673, planning deficiencies with an (RII) of 0.635, and external factors with a Relative Importance Index (RII) of 0.624. Based on the findings, this study recommends the adoption of modern construction technologies such as precast construction, drone-based surveying, and Ground Penetrating Radar (GPR) to help reduce delays in future infrastructure projects. Keywords (Fast-tracking technique, Delay mitigation, Mega infrastructure projects, Relative importance index (RII)).